An assessment of the impact of Look East Policy on Zimbabwe infrastructural development between 2003 and 2016 - Mapiko, Alfred (Midlands State University, 2017)
The study is an assessment of the effects of the Look East Policy (LEP) on Zimbabwe‘s infrastructural development.. Its aim is to collect, describe and analyse the extent to which the infrastructural development of Zimbabweans has been affected by the Look East Policy from 2003 up to 2016. The findings of the research were that the policy had yielded both tangible and intangible benefits as well as negative effects but, not without criticism and impediments. Some of the findings fuse with the theoretical framework developed earlier from the literature that was consulted. Out of the narrative emerge variables that have influenced subsequent analysis and discussion on the effects of the Look East Policy on Zimbabwe’s infrastructural development. The study contributes much to the enlightenment of the current as well as future academic figures of the infrastructural benefits as well as negative effects of the Look East Policy.